Pandemic’s Impact On Bursa Malaysia Sectors: A Comprehensive Study Utilising Olsm And Esm - Chee Kher Sin; Chew Suet Ting; Nor Aziyatul Izni; Aeshah Mohd Ali; Nur Ilyana Ismarau Tajuddin; Saufianim Jana Aksah; Chin Jia Hou (UMT Press, 2024)
Non-Indexed Publication